2015
DOI: 10.1186/1742-4755-12-s2-s12
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational description of frequency and timing of antenatal care attendance and coverage of selected interventions from sites in Argentina, Guatemala, India, Kenya, Pakistan and Zambia

Abstract: BackgroundThe Global Network for Women’s and Children’s Health Research is one of the largest international networks for testing and generating evidence-based recommendations for improvement of maternal-child health in resource-limited settings. Since 2009, Global Network sites in six low and middle-income countries have collected information on antenatal care practices, which are important as indicators of care and have implications for programs to improve maternal and child health. We sought to: (1) describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…It is evident from the results that majority of the respondents initiated their antenatal clinics in the third trimester; this is in line with studies done by Bucher et al (2015) and Linda (2015) which also found pregnant mothers to book for their antenatal clinics late in pregnancy…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is evident from the results that majority of the respondents initiated their antenatal clinics in the third trimester; this is in line with studies done by Bucher et al (2015) and Linda (2015) which also found pregnant mothers to book for their antenatal clinics late in pregnancy…”
Section: Discussionsupporting
confidence: 88%
“…Most of the men do not accompany their spouses to the clinics (Kwambai et al, 2013). In another study, pregnant women in Kenya were reported to initiate antenatal care clinics in the second and third trimesters compared to other countries which were under study (Bucher et al, 2015). Mothers feared to be reprimanded by health care providers, others cited mistimed conception, experience of previous pregnancy especially those who suffered complications motivated the pregnant mothers to initiate antenatal clinics early.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, the timing of the first visit for antenatal care is late, occurring typically late in the second trimester. 8,9 Moreover, access to ultrasonography is low, with <7% of pregnant women having access to ultrasound in rural sub-Saharan Africa. 4 Traditional sonography in late pregnancy is notably inaccurate for determining GA (±4 weeks).…”
mentioning
confidence: 99%
“…Nulliparity (22,24) Male fetus (24) Low education or literacy levels (3,22,24,27) Low socio-economic status (3,14,22,24) Younger or older age (24,27) Very low body mass index or obesity (22) Alcohol, tobacco or other drug use (23) Previous pregnancy loss (3,22) Maternal anemia (24,27) Delivery at ≥41 weeks of gestational (25) Medical care factors Lack of access to or inadequate antenatal care (21,22,45,48) Lack of access to or inadequate hospital care (21,22,43,45) …”
Section: Demographic/socio-economic Factorsmentioning
confidence: 99%
“…Simply noting that a visit took place does not indicate whether the mother was screened for Rh disease, syphilis or human immunodeficiency virus, was given a bed-net or treated prophylactically for malaria, given iron and vitamins for anemia prevention or treatment or had her blood pressure taken and urine tested for protein to diagnose preeclampsia (48). Equally important, counting the number of visits does not tell us whether any visits were performed late in the third trimester when preeclampsia and FGR often become apparent for the first time.…”
Section: Prenatal Carementioning
confidence: 99%